Mandated reporting of child abuse and neglect: a practical guide for social workers - Lau, Kenneth J. (Springer, 2009)
Introduction to mandated reporting -- The social worker as mandated reporter -- Defining child abuse and neglect -- Risk factors : the potential for child abuse or neglect -- Signs of abuse and neglect -- When is a report required? -- How to make a report -- After the report : what happens next? -- Legal and ethical issues in mandating reporting -- Legal protections and consequences for mandated reporters -- The role of law enforcement in the protection of children